Avaliação dos indicadores do potencial turístico do município de Itapipoca: subsídios para o desenvolvimento sustentável do turismo - Oliveira, Huáscar Pinto Vidal de (2009)
The tourism as an economical activity should be inserted into a larger project planning, in which the other sectors related to socioeconomics and the environment may be taken into consideration. In the state of Ceará - Brazil, this activity plays an important role in the overall economic policies, being currently inserted in the world dynamic, as an expansion activity of the financial capital that drives more and more the services and the income distribution. Itapipoca, a town located on the west coast, in the northern of the state of Ceará - Brazil is the object of this research study. It is a town that covers great landscape diversity, with different capabilities and limitations in tourist activities. The overall objective of the research considered the diversity and the lack of research focusing on tourism in a sustainable way for the local community. Thus, we proposed to evaluate the indicators of tourism potential for the town of Itapipoca as a support for development, with the need for operationalization of sustainability as well as attend the growing tourist demand by the State of Ceará, especially in the coastal region. Specifically, the Geoenvironmental and Socioeconomic framework of the area of study was characterized, the Sustainable Tourism Potential Index (IPTS), directed at the tourist activity was developed; the socioeconomic indicators of tourism in the town and the district of Whale Beach (Praia da Baleia) were evaluated. It was proposed through them a model of sustainable tourism to the area under study. The operationalized interdisciplinary approach allowed evaluating 21 sustainability indicators related to tourism, to the diversity and limitations found in the region with the aid of geotecnologies. Among the conclusions reached through the mapping of the selected indicators are: a) The need for investment in infrastructure in areas identified for greater tourism potential and b) low potential for tourism development (IPTS) influenced by low socioeconomic indicators, in areas with high demand and tourist attraction, finding areas under pressure from tourism with significant socioeconomic and environmental constraints.